The Effectiveness of Indonesian Traditional Games and Agility on Student’s Gross Motor Skills in Elementary School Hj. Isriati Baiturrahman 2 Semarang - Aribowo, Dhany Suhartantyo; Hidayah, Taufiq; Rumini, Rumini (Journal of Physical Education and Sports, 2019)
The purpose of the study is to find out and analyze (1) The Differences effect between Indonesian traditional games with and without tools on gross motor skills in fourth grade male students of Elementary School Hj. Isriati Baiturrahman 2 Semarang, (2) Differences affect between students who have high and low agility towards gross motor skills in fourth grade male students of Elementary School Hj. Isriati Baiturrahman 2 Semarang, (3) Interaction between the types of Indonesian traditional games and the agility towards gross motor skills in fourth grade male students of Elementary School Hj. Isriati Baiturrahman 2 Semarang. This study uses an experimental method with a 2x2 factorial design. The data analysis technique uses Analysis of Variants (ANOVA) at the significance level (α) = 0.05. The results of this study (1) There is a significant differences between the Indonesian traditional games using traditional tools and without using traditional tools for gross motor skills by obtaining Fvalue = 5.597 with a significance value of 0.028, with a significance level of 0.028 < 0.05, (2) There is an influence between high and low agility on gross motor skills with Fvalue = 13.159 with a significance value of 0.002, with a significance level of 0.002 < 0.05, (3) There is an interaction between Indonesian traditional games and the agility towards gross motor skills with Fvalue = 15.547 and Ftable = 3.47, this means Fvalue > Ftable.